The clinical, functional, and radiological effect of long-term used immunosuppressive therapy for post-COVID-19 interstitial lung disease : Immunosuppressive therapy in post-COVID-19-ILD - Gul, Sule; Demirkol, Barış; Eren, Ramazan; Baydili, Kursad Nuri; Babaoğlu Elkhatroushi, Burcu; Ulusan, Şerife Nur; İlhan, Umut and Çörtük, Mustafa and Çetinkaya, Erdoğan (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background and aim: Persistent interstitial lung disease (ILD) after COVID-19 infection can lead to severe loss of respiratory function and a decrease in the quality of life. There is no consensus regarding the treatment of post-COVID-19-ILD. This study aims to investigate the effectiveness of immunosuppressive treatment for this group of patients. Methods: This retrospective observational study included patients diagnosed with post-COVID-19-ILD from 2021 to 2022. Patients who had pulmonary symptoms, required prolonged oxygen therapy, and/or had restrictive pulmonary function test (PFT) and/or DLCO <80%, with diffuse parenchymal involvement on high-resolution computed tomography (HRCT), were given immunosuppressive treatment with methylprednisolone and/or mycophenolate mofetil (MMF) and followed up for 6 months. Results: Among the 48 patients, 35 were treated. Two patients were excluded due to discontinued treatment and passed away before the study period ended. Of 33 cases, 21 (66.6%) were treated with methylprednisolone, 11 (33%) with methylprednisolone + MMF, and 1 (0.4%) with MMF alone. Comparing baseline and 6th-month data revealed significant improvement in mMRC score, saturation (SpO2), FVC, FVC%, FEV%, and DLCO% values (p<0.005). While regression was observed in all radiologic findings, regression in ground glass and reticulation was statistically significant (p<0.005). When the 1st and 6th-month data were compared, a significant increase was observed in SpO2 and DLCO% values (p=0.016) and there was a significant regression in reticulation radiologically (p=0.01).Conclusions: Long-term immunosuppressive therapy may be preferred in proper cases of post-COVID-19-ILD as an effective and safe treatment option that improves the quality of life, respiratory parameters, and radiologic findings.